Sustainability, eco-efficiency, and conservation in transportation infrastructure asset management proceeding of the 3rd International Conference on Transportation Infrastructure, Pisa, Italy, 22-25 April 2014 - Losa, Massimo; Papagiannakis, A. T. (CRC Press, 2014)
Worldwide there is a growing interest in efficient planning and the design, construction and maintenance of transportation facilities and infrastructure assets. The 3rd International Conference on Transportation Infrastructure ICTI 2014 (Pisa, April 22-25, 2014) contains contributions on sustainable development and preservation of transportation infrastructure assets, with a focus on eco-efficient and cost-effective measures.